Achoo! : the Acclarent, Inc. revolution - Mukherjee, Kaushik (SAGE Knowledge. Cases., 2019)
Acclarent, Inc. is a medical devices startup backed by venture capital firms and has come up with an innovative technology for sinus treatment. The company has made significant investments in product development as well marketing to ensure that the new technology is accepted by ear, nose, and throat (ENT) surgeons and becomes part of their medical treatment procedures. Adoption by ENT surgeons has been slow. The investments have led to significant accumulated losses for Acclarent. The case study analyzes the options available to the company founder in deciding the next course of action for the startup.